The viewpoints of residents of Kerman, Iran regarding the challenges and barriers of preparing households against earthquakes: A theory-guided qualitative content analysis - Rezabeigi Davarani, Esmat; Farahmandnia, Hojjat; Khanjani, Narges; Nekoei-Moghadam, Mahmood (Frontiers in Public Health, 2022)
Introduction Earthquakes cause a lot of damage and casualties. For various reasons, most households are not prepared for earthquakes. This study aims to identify the challenges and barriers to households' preparedness against earthquakes from the viewpoint of Kerman residents. Methods This qualitative-directed content analysis study was conducted from December 2021 to May 2022 in the city of Kerman in southeast Iran. Data was collected by purposive sampling through in-depth and semi-structured individual face-to-face interviews with 48 households. Results After multiple rounds of analyzing and summarizing the data based on the social-cognitive theory and taking into consideration similarities and differences, five main categories and 19 subcategories created based on the results of data analysis and including (1) Challenges related to cognitive factors (2) Challenges related to behavioral factors (3) Challenges related to the physical environment (4) Challenges related to the social environment and (5) Challenges related to financial factors. Conclusion Although the participants listed many challenges and barriers in different fields, in order to overcome the barriers and challenges of preparing households for an earthquake, the support of the authorities and the cooperation of the residents are necessary.